2009
DOI: 10.1016/j.msea.2009.07.061
|View full text |Cite
|
Sign up to set email alerts
|

On the production and properties of novel particulate NiTip/AA2124 metal matrix composites

Abstract: a b s t r a c tNovel aluminium (AA2124) matrix composites reinforced with 10 and 20 vol.% NiTi particulates have been fabricated by using powder metallurgy processing techniques. It is shown that in the as-extruded condition the composite materials show enhanced damping capacity and improved compressive strength compared to the unreinforced material produced similarly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As discussed by Furuya [147], the implementation of SMAs leads to two potential interesting mechanisms: (i) development of compressive residual or bias stresses to increase the apparent yield strength through the pre-strain assisted SME, and (ii) application of compressive stresses around a crack tip through the SME. The increase of apparent yield strength at higher temperatures was first shown experimentally in aluminum metal matrix composites reinforced with NiTi fibers [148,8,147] and particulates [361][362][363]392]. Recently, in the interfacial layer.…”
Section: Applicationsmentioning
confidence: 92%
“…As discussed by Furuya [147], the implementation of SMAs leads to two potential interesting mechanisms: (i) development of compressive residual or bias stresses to increase the apparent yield strength through the pre-strain assisted SME, and (ii) application of compressive stresses around a crack tip through the SME. The increase of apparent yield strength at higher temperatures was first shown experimentally in aluminum metal matrix composites reinforced with NiTi fibers [148,8,147] and particulates [361][362][363]392]. Recently, in the interfacial layer.…”
Section: Applicationsmentioning
confidence: 92%
“…To predict the undesired beginning of the plastic deformation in dependence of the recovery stress of the SMA wire, it has to be estimated when the generated stress in the matrix overcomes the flow stress of the aluminum. In both components the generated stress during the bending can be calculated by equations (16) and (17) if the recovery stress σ recovery is known. The experimental investigations in section 2 have shown that the transition between a pure elastic and an elastic plastic deformation of all actuators lies between 75 °C and 100 °C.…”
Section: Analysis Of the Occurring Stressesmentioning
confidence: 99%
“…Besides the improvement of the mechanical properties, the investigations show the ability of Ni-Ti/Al composites to be used as load or strain sensors. Extrusion was used by San Martín et al [16] for processing of a composite, based on AA2124 aluminum powder, containing NiTi particles. The composites show improved strength and lower ductility compared to the nonreinforced specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The powder-metallurgy leads to a high bonding quality resulting in an increase of the yield, ultimate and shear strength as well as an increased fatigue life. San Martín et al [19] combined NiTi particles and AA2124 powder in an extrusion process. In comparison to non-reinforced specimens, the composites showed a lower ductility, higher strength as well as an improved damping capacity (Thorat et al [20]).…”
Section: Introductionmentioning
confidence: 99%